INTERPRETATION OF BAKUREH PROJECT ARCHIVES DAUR SUBUR PROGRAM #4 GUBUAK KOPI COMMUNITY INTO COLLAGE WORKS - Jonneva, Volta Ahmad; Zam, Riswel (PT. Antis International Publisher, 2024)
Collage work is the art of cutting and sticking on a flat surface, in the form of two-dimensional works of art that use various materials as a medium to create an artistic composition. In this case, the collage work comes from a program initiated by the Komunitas Gubuak Kopi entitled Daur Subur, which is an art platform as a study of the culture that develops in agricultural communities in Solok City, West Sumatra. In the Daur Subur program there is an archive of documentation collected during activities, which have been running from 2017 until now. In 2018 the Daur Subur#4 program launched a special theme entitled